2009
DOI: 10.3742/opem.2009.9.1.049
|View full text |Cite
|
Sign up to set email alerts
|

Effects of methanol extracts of Cuscuta reflexa Roxb. stem and Corchorus olitorius Linn. seed on male reproductive system of mice

Abstract: SUMMARYThe antifertility activity of methanol extract of Cuscuta reflexa Roxb. stem (MECR) and Corchorus olitorius Linn. seed (MECO) were studied on male Swiss albino mice. The extracts were found to decrease sperm count, percentage of motile sperm and testosterone level in treated mice when compared with vehicle control after 17 days of treatment. The weight of gonads, epididymis were decreased whereas no significant changes of the body weight of mice were observed after methanol extract treatments. The ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(25 reference statements)
0
3
0
Order By: Relevance
“… [ 45 ] Antifertility activity C. olitorius Seed Methanol Seed extract inhibited male reproductive capacity in sexually mature mice, since it interferes with gonadal steroidogenesis. [ 144 ] Antinociceptive, anti-inflammatory, and antipyretic C. capsularis Leaf Chloroform Reduce the number of abdominal constrictions that was confirming its traditional use of inflammatory and pain-related diseases. It is also linked to curing chronic urinary bladder inflammation.…”
Section: Biological Activitymentioning
confidence: 83%
See 1 more Smart Citation
“… [ 45 ] Antifertility activity C. olitorius Seed Methanol Seed extract inhibited male reproductive capacity in sexually mature mice, since it interferes with gonadal steroidogenesis. [ 144 ] Antinociceptive, anti-inflammatory, and antipyretic C. capsularis Leaf Chloroform Reduce the number of abdominal constrictions that was confirming its traditional use of inflammatory and pain-related diseases. It is also linked to curing chronic urinary bladder inflammation.…”
Section: Biological Activitymentioning
confidence: 83%
“…On the other hand, the fertility test by MECO treated with medium and high dose in male mice showed 100% negative results, and different dose levels resulted in a simultaneous decrease in testicular Δ 5 -3β-hydroxyl steroid dehydrogenase and glucose-6-phosphate dehydrogenase activities, both of which are involved in testicular steroidogenesis [ 144 ]. In the testis of MECO-treated mice, the activities of ascorbic acid oxidase, lactate dehydrogenase, and malic dehydrogenase were decreased, whereas carbonic anhydrase activity was significantly increased.…”
Section: Biological Activitymentioning
confidence: 99%
“…The rats because of their marked anatomical homology to the human cardiovascular system (Casteleyn et al 2017), proved valuable in psychological studies of learning and other mental processes (Vandernbergh, 2000), a study also found rats to possess metacognition, a mental ability previously documented in humans as reported by Foote et al (2007) and Wallinford et al (2010). Pal et al (2009) reported some antifertility effects of methanol extract of Corchorus olitorious while Oyedeji et al (2013) reported the antifertility effect of the aqueous extract of the plant. Thus, the study aimed to compare the effects of methanol and aqueous extracts of Corchorus olitorious leaves on some reproductive indices in male Wistar rats.…”
Section: Introductionmentioning
confidence: 99%